Evaluación del proyecto de una planta de producción de dióxido de uranio - Cadirola, R. J. C. (Comisión Nacional de Energía Atómica; Argentina, 1969)
Fil: Cadirola, R. J. C. Comisión Nacional de Energía Atómica; Argentina